Cyberincivility among Filipino Nursing Students in a public university: knowledge, experience, and acceptability - Dinero, Ella Mae; Fuentes , Irene Kathrena; Oducado, Ryan Michael F.; De la Peña , Janelle Faye; Ermita , Gabriel (Universitas Airlangga, 2023)
Introduction: The pandemic rapidly shifted nursing education to the online platform, and cybercommunication may expose students to the risk of online uncivil behaviors. Understanding cyberincivility in the primary mode of education during the pandemic is necessary. This study determined the cyberincivility knowledge, experience, and perception of acceptability among nursing students in the Philippines. Methods: A cross-sectional research design was employed with 300 Filipino nursing students of a public university who participated in the survey conducted last June 2021 using the Academic Cyberincivility Assessment Questionnaire. Data were described, and statistical differences and relationships were tested using ANOVA, t-Test, and Pearson correlation. Results: Findings indicated that nursing students generally had high knowledge (M=11.53), low experience (M=1.67), and low acceptability (M=1.41) of online uncivil behaviors. Academic cyberincivility knowledge, experiences, and acceptability did not significantly vary (p>0.05) based on sex, year level, and duration of daily internet usage. There was a significant positive moderate correlation (r=.402, p=.000) between cyberincivility experience and acceptability. Conclusions: Nursing schools should continuously strive to avoid the risk of uncivil cyberspace behaviors and promote an online culture of civility in online learning spaces.